Sufyān al-Thawrī and the Kufans - Melchert, C (Brill Academic Publishers, 2022)
Sufyān al-Thawrī (d. 161/777?) was a major Kufan jurisprudent with a later reputation for special hostility to Abū Ḥanīfa (d. 150/767) and his school and for upholding hadith against raʾy. However, the record of his hadith transmission as preserved in ninthcentury collections shows that he mainly both collected and disseminated hadith in Kufa. The record of his agreements and disagreements in law as preserved in Muḥammad ibn Naṣr alMarwazī (d. 295/907-8?), Ikhtilāf al-fuqahāʾ, Ibn al-Mundhir (d. 318/930-1?), al-Ishrāf, and al-Jaṣṣāṣ al-Rāzī (d. 370/981), Mukhtaṣar Ikhtilāf al-ʿulamāʾ, shows preponderant agreement with the Ḥanafiyya, a lower degree of agreement with, among others, al-Awzāʿī and alShāfiʿī. The biographical dictionaries record few traces of a personal school of law after him. Doubts have been raised, but in the end he is to be counted an adherent of the Kufan regional school of law.